Coffee Consumption and Mortality among United States Adults: A Prospective Cohort Study - Zhou, Bingjie; Ruan, Mengyuan; Pan, Yongyi; Wang, Lu; Zhang, Fang Fang (The Journal of nutrition, 2025)
Although coffee consumption has been associated with a variety of health benefits, it remains unclear whether the addition of sugar and saturated fat modifies these effects. This study aimed to examine the relationship between coffee intake, including the amount of added sugar and saturated fat, and mortality among United States adults. We conducted a prospective cohort study using data from the National Health and Nutrition Examination Survey from 1999 to 2018, linked to National Death Index Mortality Data. The study included 46,222 adults aged 20 y and older who completed valid first-day 24-h dietary recalls. Coffee consumption was categorized by type (caffeinated or decaffeinated) and by sugar (<2.5 g per 8-oz), and saturated fat content (<1 g per 8-oz). Mortality outcomes included all-cause, cancer, and cardiovascular disease (CVD) mortality. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality risk based on type, intake levels (nondrinkers, <1 cup/d, 1 to <2 cups/d, 2 to <3 cups/d, and ≥3 cups/d) and the amount of added sugar and saturated fat. Over a median follow-up of 9.3–11.3 y, a total of 7074 deaths occurred, including 1176 cancer-specific and 1089 CVD-specific deaths. Higher coffee consumption was associated with lower all-cause mortality [HR (95% CI): 0.89 (0.78, 1.02) for < 1 cup/d; 0.84 (0.77, 0.92) for 1 to <2 cups/d; 0.83 (0.75, 0.93) for 2 to <3 cups/d; and 0.85 (0.77, 0.95) for ≥3 cups/d; P-trend = 0.004]. However, the mortality benefits were restricted to black coffee [HR (95% CI): 0.86 (0.77, 0.97)] and coffee with low added sugar and saturated fat content [HR (95% CI): 0.86 (0.75, 0.99)]. The health benefits of coffee consumption may be diminished when sugar and saturated fat are added.